Codename TREVI. Terrorismusbekämpfung und die Anfänge einer europäischen Innenpolitik in den 1970er Jahren - Oberloskamp, Eva (2016)
Terrorism became an international problem in the 1970s, forcing the nine states in the European Community to cooperate in the realm of domestic security. The so-called TREVI meeting set the direction for the development of European domestic security policy. The author shows that the meeting was a pragmatic response to terrorism while at the same time, an instrument of broader integration efforts.